Serum High-Sensitivity C-Reactive Protein Levels in Women with Polycystic Ovary Syndrome: A Case-Control Study - Malluru, Naga Tejaswini; Agarwal, Rajni; Sharma, Mridula (International Journal of Medical Research, 2026)
Introduction: Polycystic Ovary Syndrome is a prevalent endocrine disorder marked by reproductive and metabolic disturbances, often accompanied by chronic low-grade inflammation. High-sensitivity C-reactive protein (hs-CRP) has gained attention as a potential marker reflecting this inflammatory burden and its metabolic consequences. This study aimed to assess the diagnostic value of hs-CRP and its association with clinical features in women with PCOS. Method: A case-control study was done over one year at a tertiary care center, including 42 women diagnosed with PCOS based on Rotterdam criteria and 83 age-matched healthy controls. Demographic, anthropometric, clinical, and biochemical parameters were recorded. hs-CRP levels were estimated using standardized laboratory methods. Statistical analysis included independent t-tests, chi-square tests, and ROC curve analysis, with p < 0.05 considered significant. Result: PCOS patients had significantly higher hs-CRP levels (3.9 ± 3.6 mg/L) than controls (1.0 ± 1.1 mg/L; p < 0.001). ROC analysis showed good diagnostic performance (AUC 0.827). A cutoff of 1.17 mg/L showed 85.7% sensitivity and 68.7% specificity. Dysmenorrhea showed a significant association with higher hs-CRP categories, while other symptoms showed non-significant trends toward elevated levels. Conclusion: hs-CRP is a valuable marker for identifying inflammatory and metabolic risk in PCOS and may support early risk stratification.